Chapter Multilingualism, Multiscripturalism, and Knowledge Transfer in the Dead Sea Scrolls and Graeco-Roman Judaea - Popović, Mladen (Judaism, Christianity, and Islam - Tension, Transmission, Transformation, 2018)
How did ancient communities approach the concept of religious knowledge? Was it something to be shared with all, or was it the provenance of certain initiates? This volume of collected essays illustrates a range of approaches to this dilemma, from ancient Babylon, Judaism (Dead Sea scrolls, Book of Jubilees, rabbinic traditions in the Roman Empire), Christianity (Gnosticism, Alexandria, Gospel of John) and Islam (Qur'ān and Ismaili traditions).